2016
DOI: 10.1369/0022155416667928
|View full text |Cite
|
Sign up to set email alerts
|

Differential Lectin Binding Patterns Identify Distinct Heart Regions in Giant Danio (Devario aequipinnatus) and Zebrafish (Danio rerio) Hearts

Abstract: SummaryLectins are carbohydrate-binding proteins commonly used as biochemical and histochemical tools to study glycoconjugate (glycoproteins, glycolipids) expression patterns in cells, tissues, including mammalian hearts. However, lectins have received little attention in zebrafish (Danio rerio) and giant danio (Devario aequipinnatus) heart studies. Here, we sought to determine the binding patterns of six commonly used lectins-wheat germ agglutinin (WGA), Ulex europaeus agglutinin, Bandeiraea simplicifolia lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…20,[23][24][25] Although Ulex europaeus agglutinin I strongly labels blood vessels in human tissues, rodents do not express ligands for Ulex europaeus agglutinin I on their blood vessel walls, 26,27 so this lectin is not suitable for animal models. Tomato lectin (TL; Lycopersicon esculentum agglutinin) recognizes poly-N-acetyl lactosamine-type oligosaccharide moieties 28,29 that is relatively specific for microvessels [30][31][32][33] in mice. 34,35 We are not aware of any published reports of TL perfusion for the assessment of normal choroidal vasculature in flat mounts, but it has been described for hyaloidal vessel analysis and choroidal neovascularization detection in the subretinal space.…”
Section: Introductionmentioning
confidence: 99%
“…20,[23][24][25] Although Ulex europaeus agglutinin I strongly labels blood vessels in human tissues, rodents do not express ligands for Ulex europaeus agglutinin I on their blood vessel walls, 26,27 so this lectin is not suitable for animal models. Tomato lectin (TL; Lycopersicon esculentum agglutinin) recognizes poly-N-acetyl lactosamine-type oligosaccharide moieties 28,29 that is relatively specific for microvessels [30][31][32][33] in mice. 34,35 We are not aware of any published reports of TL perfusion for the assessment of normal choroidal vasculature in flat mounts, but it has been described for hyaloidal vessel analysis and choroidal neovascularization detection in the subretinal space.…”
Section: Introductionmentioning
confidence: 99%
“…The hearts were washed and stained immediately. Fluorescein-conjugated and rhodamine-conjugated BS lectin, Con A, or wheat germ agglutinin (WGA) (Vector Laboratories, Burlingame, CA, USA) were used as previously described [ 37 ]. Hearts and larvae were incubated wholemount in Cellstar 24 well cell culture plates (Santa Cruz, Biotech, Santa Cruz, CA, USA) overnight at 4 °C using in 400 μL of lectin-containing Tris buffer saline (50-mM Tris, 150-mM NaCl, 1-mM CaCl2, 1-mM MgCl 2 , pH 7.6) at the following final lectin concentrations: BS lectin (1:400, 5 μg/mL), Con A (1:1000, 2 μg/mL), WGA (1:1000, 2 μg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Studies in our lab have shown that the heart of an adult giant danio ( D. cf aequipinnatus ) possesses robust regenerative capacities similar to those seen in the zebrafish [ 36 ]. Recently, we reported on the use of lectins as histochemical tools to study cardiac biology in giant danio and zebrafish [ 37 ]. However, little is known regarding the cardiac development, growth and maturation of Devario species.…”
Section: Introductionmentioning
confidence: 99%
“…We first serendipitously observed an area on the superior aspect of 3-day postfertilization D. malabaricus larval head, highly reactive to wheat germ agglutinin (WGA), and Ricinus communis agglutinin I (RCA-I), (not shown), while carrying experiments for comparative cardiac development using lectin histochemistry. 36 Closer inspection under brightfield microscopy revealed the profile of an oval shaped and markedly raised protuberance over the dorsal epithelial surface of the larval head ( Figure 4A-E). We identified this structure to be the mucus producing cement gland of the species and studied its development from hatching up to 3 weeks post fertilization (wpf).…”
Section: Lectin Reactivity In Cement Gland In the Late Embryonic Anmentioning
confidence: 99%
“…For whole-mount embryos and larvae imaging, sample were fixed in 4% paraformaldehyde, washed in 1X PBS, and permeabilized with 0.5% Triton X-100 in 1X PBS overnight at 4 C. Fluorescein-conjugated and rhodamine-conjugated lectins (Vector Laboratories, Burlingame, California) were used. Larvae were incubated in Cellstar 24-well cell culture plates (Santa Cruz, Biotech, Santa Cruz, California) overnight at 4 C, as previously described 36 using in 400 μL of lectincontaining Tris buffer saline (50-mM Tris, 150-mM NaCl, 1-mM CaCl2, 1-mM MgCl2, pH 7.6) at final concentrations between 2 and 5 μg/mL. Next, larvae were washed in PBS, and cell nuclei were stained with Hoechst stain (Invitrogen, Eugene, Oregon), wash in 1X PBS.…”
Section: Wholemount Lectin Staining and Immunostaining Proceduresmentioning
confidence: 99%